Analisis Kinerja Kepala Desa Dan Badan Permusyawaratan Desa Dalam Pembangunan Infrastruktur Desa : Studi Kasus Desa Nduaria Kecamatan Kelimutu Kabupaten Ende Propinsi NTT - Damianus Tola; Angelus K. Subagio (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the work performance of the Village Head and the Village Consultative Body (BPD) in the development of village infrastructure. The data collection process in this study used interview, observation and documentation techniques as field evidence. The research took place in Nduaria Village, Kelimutu District, Ende Regency. Based on field data, it was found that 8 village infrastructure development programs that were realized reached 100 percent completion and 6 work programs had not been realized due to lack of funds and waiting for the next stage of village fund disbursement. This factor is an obstacle to the infrastructure development process in Nduaria Village